Menyikapi perubahan perilaku remaja - Kenny Dwi Fhadila (JPGI (Jurnal Penelitian Guru Indonesia), 2017)
Behavior change is a process that happens at any time and can not be avoided. Most of these behavioral changes take place over time. Behavior can be exemplified like laughing, drinking and so forth. Nor is indirect behavior also in the form of thoughts and feelings. Many things in the know of behavior change is something that makes a person change from the previous pattern. Adolescence is very close to behavioral changes. Adolescence is a period in which children's adolescent become adult. Adolescence is synonymous with puberty, teenagers who were previously children in this period began to learn to find the true identity. From this began to arise a variety of changes in adolescent behavior. Not infrequently we encounter changes during puberty, such as changes in behavior that is not as usual. Many parents find a change in their child during puberty. Sometimes children behave as usual and selanjutanya not take long behavior change quickly, or often called adolescent puberty behave depends on the mood. As a child is often aloof, gregarious, wanting freedom and others. So from here, making this paper aims to help parents to critically address and analyze behavior change in adolescent puberty. Help readers recognize the changes that occur when adolescence is in puberty.